2004
DOI: 10.1089/108729104323076034
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to Antiretroviral Therapy in HIV-Positive Patients in Costa Rica

Abstract: A cross-sectional study was performed among seropositive individuals who sought HIV treatment at an outpatient clinic in San Jose, Costa Rica, to determine the prevalence, predictors, and reasons for nonadherence to antiretroviral. A structured, face-to-face interview was administered to 88 patients. The primary outcome of adherence was measured as taking 100% of medications within 3 days prior to interview. A number of risk factors, including demographic information, HIV knowledge, logistics of the regimen, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…While adherence to ART has been widely studied in resource-rich settings [7][8][9][10][11][12], fewer studies have been conducted on adherence in the developing world -in Africa [13], Latin and Central America [14,15] and more recently China [16]. A systematic literature search for adherence studies in the Pacific revealed none.…”
Section: Introductionmentioning
confidence: 99%
“…While adherence to ART has been widely studied in resource-rich settings [7][8][9][10][11][12], fewer studies have been conducted on adherence in the developing world -in Africa [13], Latin and Central America [14,15] and more recently China [16]. A systematic literature search for adherence studies in the Pacific revealed none.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies reported that long travel distances are a potential barrier to accessing services and, after starting ART, they are a barrier to optimal adherence. [4][5][6] To improve accessibility, ART services need to be located as close to the community as possible. Thus, Mumbwa district health management team introduced a mobile ART service at rural health centres as a pilot programme of the Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%
“…18, 27 In addition, we did not have the necessary data to weight distance measures by costs associated with travel (e.g., car, bus, bicycle, foot). This analysis thus assumes that potential modes of transportation have no influence on PMTCT uptake, which may not be realistic, 28 since cost would likely increase with distance.…”
Section: Discussionmentioning
confidence: 99%